2004
DOI: 10.1016/j.ijrefrig.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal conduction in microchannel gas coolers for carbon dioxide

Abstract: A numerical code was developed for an accurate fully three-dimensional simulation of crossflow compact heat exchangers with finned, internally microchannelled flat tubes, which are often used as gas coolers in transcritical refrigerating machines CO 2 operated. The equations describing the system were discretised by means of a finite-volume and finite-element hybrid technique for strictly adhering to the real heat transfer process regarding the finned surfaces. The numerical code uses recent correlations by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…It does not account for 2D longitudinal heat conduction in the tube and it neglects the longitudinal heat conduction in the fin, along the air flow direction. Asinari et al (2004) concluded that these effects produce a negligible effect on the performance of the class of CO 2 gas cooler they studied.…”
Section: Literature Review and Backgroundmentioning
confidence: 97%
See 4 more Smart Citations
“…It does not account for 2D longitudinal heat conduction in the tube and it neglects the longitudinal heat conduction in the fin, along the air flow direction. Asinari et al (2004) concluded that these effects produce a negligible effect on the performance of the class of CO 2 gas cooler they studied.…”
Section: Literature Review and Backgroundmentioning
confidence: 97%
“…This capability means a model able to simulate both scenarios with and without fin cut. Asinari et al (2004) proposed a three-dimensional model for microchannel gas coolers using CO 2 as refrigerant which can evaluate such effects but the model employs a finite-volume and finite-element hybrid technique. This model discretizes the equations by means of a finite-volume and finite-element hybrid technique taking into account longitudinal heat conduction (LHC) along all directions for all elements (fins and tubes), thus it does not employ the adiabatic-fintip assumption.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%
See 3 more Smart Citations